Possibilities and limitations for the back analysis of an event in mountain areas on the coast of São Paulo State, Brazil using RAMMS numerical simulation - dos Santos Corrêa, Claudia Vanessa; Vieira Reis, Fábio Augusto Gomes [UNESP]; do Carmo Giordano, Lucília [UNESP]; Cabral, Victor Carvalho [UNESP]; Targa, Débora Andrade [UNESP]; Brito, Hermes Dias [UNESP] (My University, 2019)
Debris flows are mass movements that develop along drainage networks and involve generally dense fluids, compose of materials of different grain sizes, as well as woods and variable amounts of water, identified as natural processes that constitute the dynamics and the modeling of the landscape. The areas most susceptible to the occurrence of these processes in Brazil are in the foothills of the Serra do Mar, Serra da Mantiqueira and the Serra Geral, and on the north coast of São Paulo State. In 03/18/1967 there was an important landslide and debris-flows which affected the region of Caraguatatuba and São Sebastião. In this area, there is a pipeline network associated with Petrobras Treatment Units, other enterprises, structures and a large urban area in growth. The aim of this work is to show the results of the back-analysis of the debris-flow events that occurred in 1967 in a mountain area in the Serra do Mar in Caraguatatuba region (São Paulo State, Brazil) with RAMMS numerical simulation, using calibrated input parameters. The inputs were viscosity, DEM, landslide scars as release areas, the density of the debris-flow material, duration of debris-flow process and orthophoto. The modeling results were compared with the deposit area mapped in aerials photos, which was established zones of iso-thickness of the materials. The results showed a good correlation between the area and thickness of deposition modeled and observed. Moreover, the fieldwork and the retro-analysis studies revealed that the Serra do Mar debris flows have a predominantly granular rheological flow and the modeling results showed that the deposition zones are given preferably in regions with slope less than 5º.
Keywords: Brazil; Numerical simulation; RAMMS model; Serra do Mar